The essence and functions of cryptocurrencies - Panahov, F. (Економічний вісник Донбасу, 2022)
With the development of electronic systems, ideas have repeatedly arisen to create an electronic analogue of cash for remote payment. Cryptocurrency technology was originally aimed at the absence of a trusted node - one whose actions are guaranteed to be true and who can confirm the correctness of other people's operations. For the first time, this problem was solved in the Bitcoin system due to the artificial complication of making changes to the transaction history register. З розвитком електронних систем неодноразово виникали ідеї щодо створення електронного аналога готівки для дистанційної оплати. Технологія криптовалюти спочатку була націлена на відсутність довіреного вузла – того, чиї дії гарантовано відповідають дійсності і який може підтвердити правильність операцій інших людей. Вперше ця проблема була вирішена в системі Bitcoin за рахунок штучного ускладнення внесення змін до реєстру історії транзакцій.